Feasibility indicators of telemedicine for patients with dementia in a public hospital in Northeast Brazil during the COVID-19 pandemic. - Danielle Pessoa Lima; Ingrid Barros Queiroz; Alexandre Henrique Silva Carneiro; Daniela Araújo Aragão Pereira; Camila Silva Castro; Antonio Brazil Viana-Júnior; Charlys Barbosa Nogueira; João Macedo Coelho Filho; Rômulo Rebouças Lôbo; Jarbas de Sá Roriz-Filho; Pedro Braga-Neto (PLoS ONE, 2022)
Background The use of telemedicine has become a fundamental tool in healthcare in recent years, especially at times of Covid-19 pandemic. Currently, there are several telemedicine tools that are simple, inexpensive, and effective means of communication. This article aims to describe indicators of feasibility including patient recruitment, attendance, discomfort (internet connection issues and/or noncompliant patient behavior), satisfaction, and travel time and cost savings of virtual telemedicine consultations for patients with dementia. Methods The study was conducted at the Geriatrics Department of Hospital Universitário Walter Cantídio (HUWC) in Fortaleza, Brazil, between May 1st and December 31, 2020. The eligibility criteria included previous diagnosis of dementia syndrome and receiving care at the hospital's dementia outpatient clinic in face-to-face consultations in the preceding 12 months. Patients were excluded if they did not feel comfortable with virtual consultations, did not have the required communication technology available or their caregiver was not available to attend the remote consultation. The patients were recruited from the outpatient dementia clinic's medical appointment scheduling list. The intervention was designed as a one-time consultation and it included treatment approaches and health promotion recommendations. Results Patient recruitment, attendance and discomfort rates were 85.5%, 97.7% and 9.4%, respectively. To attend face-to-face visits, they reported an average travel time (including the consultation) of 233.21 minutes and average total cost of 60.61 reais (around USD 11). The study intervention was well accepted among the patients and their caregivers with 97.6% being satisfied. Many were happy to avoid long waits in crowded medical waiting rooms and the risk of covid-19 contagion. Conclusions We found good recruitment, attendance, and acceptance rates of remote care for the follow-up of dementia patients as well as low discomfort rates. Trial registration Brazilian Trial Registry (REBEC) RBR-9xs978.